Characteristics of Pregnant Women Satisfying the Universal Two-Child Policy Requirements in China: A Retrospective Cohort Study - Tang, Li; Li, Chun-Rong; Luo, Tong-Yong; Lin, Yong-Hong; Song, Wei; Wang, Zhiqiang; Lan, Qingfu; Qin, Shiji (Current Women's Health Reviews, 2024)
Background: China officially launched the universal two-child policy in January 2016. No studies in China have examined the characteristics of pregnant women since the implementation of the new family planning policy. Methods: We conducted a retrospective cohort study in Chengdu, China, to examine pregnant women's sociodemographic and obstetric characteristics satisfying the new policy requirements. Two thousand pregnant women were enrolled in the case group, 2016-2017. The comparison group included 2,000 pregnant women from the same institutions. Maternal and clinical information was extracted from medical records. Results: Compared to comparisons, the case group tended to have a higher household income and work in a non-state-owned enterprise/institution. Additionally, cases were more likely to be older (OR=1.36; 95% CI 1.09-1.70), have a history of cesarean section (OR=31.68; 95% CI 24.76-40.54), and suffer from gestational hypertension (OR=3.35; 95% CI 1.56-7.19), gestational diabetes mellitus (OR=1.61; 95% CI 1.24-2.10) and placenta previa (OR=4.45; 95% CI 2.70-7.34) than comparisons. Conclusion: We suggest emphasizing the importance of reproductive counseling and assessment, particularly targeting those satisfying the universal two-child policy requirements.
Keywords: obstetrics